2003
DOI: 10.4314/tjpr.v2i1.14580
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive property of kaolin in some drug formulations

Abstract: Purpose: Kaolin is a known adsorbent, has lubricant property in powders and is therefore proposed as a lubricant in tablet formulations. This study was carried out to evaluate whether kaolin can adsorb some active drugs when mixed with them in tablet formulations even at very low concentrations. Method: Chloroquine and chlorpheniramine tablets were formulated with powder mixtures containing various concentrations of kaolin. The effect of kaolin on the physical properties of the tablets were examined and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…The water solubility measurements of the binary mixtures (Fig. 11) have shown a slight decrease in drug solubility for I 1 K 1 and I 1 K 3 mixtures; this can be explained by the adsorption effect of kaolin which is insoluble in water [11,13]. Such water solubility attenuation occurred for several drug/ kaolin formulations [12].…”
Section: Water Solubility Investigationsmentioning
confidence: 91%
See 1 more Smart Citation
“…The water solubility measurements of the binary mixtures (Fig. 11) have shown a slight decrease in drug solubility for I 1 K 1 and I 1 K 3 mixtures; this can be explained by the adsorption effect of kaolin which is insoluble in water [11,13]. Such water solubility attenuation occurred for several drug/ kaolin formulations [12].…”
Section: Water Solubility Investigationsmentioning
confidence: 91%
“…However, many studies have shown that a decrease in drug solubility can be resulted from adsorption effect and strong interactions between kaolin and drug molecules. This critical aspect was obtained for several pharmaceutical products, e.g., ampicillin, cloxacillin, amoxicillin, clavulanic acid, chloroquine, chlorpheniramine [11], ciprofloxacin, chloroquine, piperazine, phyllocontin, digoxin and diazepam [12], metronidazole [13]. This could undoubtedly limit, in some cases, the use of kaolin in pharmaceutical formulations.…”
Section: Introductionmentioning
confidence: 97%
“…Interaction studies between silicate and some hydrophobic molecules showed that the positive charges on the molecules promote adsorption onto silica molecules. 15 Zidovudine essentially has nitrogen atoms in its chemical structure and these provide the binding sites for the silica in magnesium trisilicate. The degree of the adsorption is also dependent on the number of free binding sites available.…”
Section: Resultsmentioning
confidence: 99%
“…There are many reports of adsorbed drugs and chemicals onto kaolin, for example; quinidine (Bucci et al, 1981), propranolol (Al-Gohary et al, 1987), mebeverine hydrochloride (al Gohary, 1997); ampicillin, cloxacillin, amoxicillin, clavulanic acid, chloroquine, chlorpheniramine (Onyekweli et al, 2003), Congo red (Vimonses et al, 2009); ciprofloxacin, chloroquine, piperazine, phyllocontin, digoxin and diazepam (Hassan and Ibrahim, 2011).…”
Section: Introductionmentioning
confidence: 99%